PENGARUH PENGALAMAN BERWIRAUSAHA DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA PEMUDA STT WISMA BAHARI DESA ADAT SEMANA ABIANSEMAL - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Wijaya, Bagus Arya; Meryawan, I Wayan; Ade Krisna, I Putu Pande (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
Entrepreneurial interest is one of the important elements that determine in running a business. In creating entrepreneurial interest, severaldetermining variables are entrepreneurial experience and entrepreneurial motivation. The existence of concerns and problems encountered related toentrepreneurial experience and entrepreneurial motivation in an effort to increase entrepreneurial interest, it is appropriate in this study to investigate further on entrepreneurship experience and entrepreneurial motivation on entrepreneurial interest of youths at STT. Wisma Bahari Desa Adat Semana. The purpose of the study was to determine the simultaneous or partial effect of entrepreneurial experience and entrepreneurial motivation onthe entrepreneurial interest of youths at STT. Wisma Bahari Desa Adat Semana. The number of samples was determined by purposive sampling method, amounted of 94 members of STT. Wisma Bahari Desa Adat Semana. Data were analyzed using classical assumption test, multiple linear regression analysis, multiple correlation analysis, determination analysis, simultaneous significance test (F-test) and partial significance test (t-test). The findingshows that there is a simultaneous positive and significant effect of entrepreneurial experience and entrepreneurial motivation on the entrepreneurialinterest of youths at STT. Wisma Bahari Desa Adat Semana. While partially entrepreneurship experience has a positive and significant effect on theentrepreneurial interest of youths at STT. Wisma Bahari Desa Adat Semana. Partially, entrepreneurial motivation has a positive and significant effect on the entrepreneurial interest of youths at STT. Wisma Bahari Desa Adat Semana